2023
DOI: 10.1097/prs.0000000000010306
|View full text |Cite
|
Sign up to set email alerts
|

“The Cost of Doing Business: An Appraisal of Relative Value Units in Plastic Surgery and Other Surgical Subspecialties”

Abstract: Background: The relationship between procedural complexity and relative value units (RVUs) awarded has been studied within some specialties, but it has not yet been compared across different surgical disciplines. This study aims to analyze the association of RVUs with operative time as a surrogate for complexity across surgical specialties, with a focus on plastic surgery. Methods: A retrospective review of surgical cases was conducted with the 2019 Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…A previous study demonstrated that plastic surgery, when compared with other surgical subspecialties, had the lowest average wRVU despite the longest operative times. 19 This further supports the relative devaluation of plastic surgery as a surgical subspecialty and can easily result in further reduction of caseload. Reduction in caseload by dedicated subspecialty providers may result in a substantial reduction in patient access.…”
Section: Discussionmentioning
confidence: 60%
“…A previous study demonstrated that plastic surgery, when compared with other surgical subspecialties, had the lowest average wRVU despite the longest operative times. 19 This further supports the relative devaluation of plastic surgery as a surgical subspecialty and can easily result in further reduction of caseload. Reduction in caseload by dedicated subspecialty providers may result in a substantial reduction in patient access.…”
Section: Discussionmentioning
confidence: 60%
“…Prior observations indicate that plastic surgeons receive lower payments for physician work per hour than other surgeons. 5,6 Stoffel et al discussed that reimbursement for plastic surgery may not sufficiently account for physician work, particularly with respect to the increased operative time and surgical complexity encountered today. Variation in reimbursement per RVU may be explained by the fact that it is challenging to accurately quantify physician work, leading to some codes reflecting the amount of physician work involved more accurately than others.…”
mentioning
confidence: 99%